Modeling and simulation of new configuration of dynamic voltage restorer for power quality improvement - Omar, Rosli; Abdul Rahim, Nasrudin (SAGE PUBLICATION, 2011)
The dynamic voltage restorer (DVR) is a custom device that is used to maintain the voltage at the load terminals from various power quality problems from a disurbed incoming supply. In this paper, a novel control strategy is described for mitigation of voltage sags and swells on sensitive loads. The new control of the compensation voltages in the DVR based on the dq0 algorithm is discussed. The MATLAB/SIMULINK SimPower System toolbox has been used to obtain simulation results in order to verify the proposed scheme. From the results, it shows that the DVR is able to compensate the voltage sag or swell at sensitive loads by injecting an appropriate voltage through the injection transformer.